Comparative Study on Lossless Data Compression Techniques - Priyanka Anand, Seema (International Journal of Scientific Research and Management (IJSRM), 2017)
Image compression is a technique which removes the extraneous or unrelated information. For compression and decompression, a number of techniques such as Shannon Fano Technique, Lempel Ziv Welch, Run length Coding technique, Huffman technique etc. have been applied. In this paper, the different lossless image compression techniques have been studied. Further, a Comparative study on various techniques has been carried out and found that Embedded Zero tree Wavelet (EZW) and Set Partition in Hierarchical Transform (SPIHT) techniques perform better in terms of Compression Ratio (CR), Peak Signal To Noise Ratio (PSNR) and Mean Square Error (MSE)